Formation of trihalomethanes during the disinfection process in the potabilisation of water. - Bracho, Nibis; Castillo, Javier; Vargas, Luis; Morales, Ricardo (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
The purpose of water disinfection is to selectively eliminate pathogenic microorganisms. The aim of this work is to diagnose the conventional injection system of chlorine in the Plant Alonso de Ojeda (Plant “C”) of Maracaibo city to determine the bacteriological quality of both the natural and the treated water, as well as the formation of THMs during this process. To compare them with the permissible maximum levels of chloroform indicated by the W.H.O. (30 Î¼g/L). The applied methodology consisted on making operational changes to diminish the THMs analysing: a) condition of traditional operation, which includes pre-chloration, intermediate chloration (before the filters), b) eliminating the pre-chloration, c) post-chloration, d) modifying the pre- chloration point toward the entrance of the flocculators in absence of intermediate chloration. For each case it was determined colour, turbidity, aerobic heterotrophic, total and fecal coliforms and trihalomethanes. Being obtained in the natural waters an average of 89.17 UFC/100 mL and 3.0 UFC/100 mL for the total and fecal coliforms respectively, 508.65 UFC/100mL of aerobic heterotrophic, 5 NTU and 16 Pt-Co. Chlorine injection give as result the formation of 32.43 Î¼g/L of chloroform, when the maximum thing permissible it corresponds at 30 Î¼g/L. The elimination of the points of injection of chlorine, in the pre- chloration and the intermediate chloration, allows the chloroform reduction from 32.43 Î¼g/L to 10.57 Î¼g/L fulfilling the permissible levels. On the other hand chlorine economic expenses were decreased 50%. In this evaluation it was proven that the THMs were linearly increased at each injection point. Therefore, when suppressing the pre- chloration and the intermediate chloration, 67% of THMs were eliminated.